Phenological time lapse images from canopy camera MC108 in Sodankylä Pine stand ... - Aurela, Mika; Linkosalmi, Maiju; Tanis, Cemal Melih; Arslan, Ali Nadir; Rainne, Juuso; Kolari, Pasi; Böttcher, Kristin; Peltoniemi, Mikko (Zenodo, 2020)
This record contains phenological time lapse images from camera Sodankylä Pine stand. Camera was mounted at canopy view level at location 67.3618;26.638167(N;E, WGS84). First set of images were taken between 22.05.2014--31.12.2016 (Version 1). Subsequent Versions extend the record with newer images, and the version number indicates the years covered by the record. Cameras were set to fix white balance, brightness automatically adjusted by camera.Image have equal resolution throughout the time series, time indicated in UTC+2. Images are taken half-hourly during fixed day-time period over the year. Gaps in time series and dark images possibly exist. More details on the camera installations and operation history can be found at DOI 10.5281/zenodo.777952 The cameras were set up and images collected under EU Life+ (LIFE ENV/FI/000409) Monimet project, http://monimet.fmi.fi. For further information contact mika.aurela@fmi.fi and ali.nadir.arslan@fmi.fi ... : The cameras were set up and images collected under EU Life+ (LIFE ENV/FI/000409) Monimet project, http://monimet.fmi.fi. ...